An??lise do metagenoma viral de amostras de fezes humanas do Distrito Federal - Santos, Rayane Nogueira dos (2015)
Acute gastroenteritis, especially in developing countries, is a major cause of mortality and morbidity, which affects people of all social classes. The knowledge of etiological agent assists the choice of a treatment strategy, but also directs epidemiological studies for control measures and disease prevention, as the development of vaccines and diagnostic tests. Metagenomic approaches enable the detection of viral sequences to determine the virus population present in the stool. The objective of this study was to evaluate the viroma of human feces in 4 distinct groups, consisting of diarrheal stool samples from children, diarrheal from adults, no diarrhea from adults and immunocompromised, identifying likely pathogens involved in cases of gastroenteritis. The viral metagenomic execution method consists of the semi-purification, extraction of RNA and DNA, amplification of RNA and DNA, library construction, sequencing and analysis of the data by bioinformatics. In the analysis of the first group were detecting bacteriophages, astrovirus and torque teno virus; in the second group were identified, among others, bacteriophages, adenoviruses and torque teno virus; the third group of viruses Circoviridae family and bacteriophages; in the fourth group adenovirus, torque teno virus, gyrovirus and human papillomavirus. These results emphasize what has been identified in the literature and provides evidence that viral metagenomics has facilitated advances in the field of virology, for being a sensitive technique for the detection of viruses which can not be identified by traditional culture.Acute gastroenteritis, especially in developing countries, is a major cause of mortality and morbidity, which affects people of all social classes. The knowledge of etiological agent assists the choice of a treatment strategy, but also directs epidemiological studies for control measures and disease prevention, as the development of vaccines and diagnostic tests. Metagenomic approaches enable the detection of viral sequences to determine the virus population present in the stool. The objective of this study was to evaluate the viroma of human feces in 4 distinct groups, consisting of diarrheal stool samples from children, diarrheal from adults, no diarrhea from adults and immunocompromised, identifying likely pathogens involved in cases of gastroenteritis. The viral metagenomic execution method consists of the semi-purification, extraction of RNA and DNA, amplification of RNA and DNA, library construction, sequencing and analysis of the data by bioinformatics. In the analysis of the first group were detecting bacteriophages, astrovirus and torque teno virus; in the second group were identified, among others, bacteriophages, adenoviruses and torque teno virus; the third group of viruses Circoviridae family and bacteriophages; in the fourth group adenovirus, torque teno virus, gyrovirus and human papillomavirus. These results emphasize what has been identified in the literature and provides evidence that viral metagenomics has facilitated advances in the field of virology, for being a sensitive technique for the detection of viruses which can not be identified by traditional culture.